Mechanical properties of right-angle couplers in steel tube–coupler scaffolds. (October 2016) - Jia, Li; Liu, Hongbo; Chen, Zhihua; Liu, Qun; Wen, Suolin
Abstract: The mechanical property of right-angle couplers has a significant effect on the load bearing properties and stability of steel tube–coupler scaffolds. This paper presents a systematic and comprehensive experimental study on slipping and rotational stiffness in the right-angle coupler connection. Different influencing factors, such as bolt tightening torques, condition of components (new or old), different coupler combinations, and loading patterns, were considered. The failure modes and slipping or rotational stiffness were discussed and compared. Several conclusions were obtained. First, the anti-slipping capacity and rotational stiffness of various right-angle coupler connection styles are key parameters for the future design of steel tube–coupler scaffolds. Second, the slipping resistance and rotational stiffness of right-angle couplers increase with bolt tightening torque. However, with a high tightening effect, such couplers are likely to experience fracture failure. Third, the multi-coupler connecting method effectively strengthens slipping resistance. An old tube or old coupler degrades the overall performance of the scaffold connections. Fourth, a right-angle coupler connection demonstrates a semi-rigid performance, and an old coupler has weaker rotational stiffness than new ones. Lastly, fracture mostly occurs in the bolt connecting region and at the boundary between the cover plate and base plate, as revealed by slipping and rotational stiffness tests. These areas require special care during actual application. Highlights: The mechanical properties of right-angle coupler have big dispersion. The multi-coupler connecting method effectively strengthens slipping resistance. Used wear makes the mechanical properties of coupler degradation seriously. Standard coupler is a semi-rigid joint with rotational stiffness of 12–30 kN·m/rad.